Adhesion of carbon steel and natural rubber by functionalized silane coupling agents. (January 2017) - Sang, Jing; Aisawa, Sumio; Miura, Katsuya; Hirahara, Hidetoshi; Jan, Oravec; Jozef, Preto; Pavol, Melus
Abstract: This study characterized a method of adhesion between uncured natural rubber and carbon steels (CS) by the surface modification of the CS with silane coupling agents comprising amino, thiol, glycidoxy, and isocyanate organic functionality. The effects of the functionalization of the silane coupling agents on adhesion between CS and uncured natural rubber were investigated by X-ray photoelectron spectroscopy, Fourier transform infrared spectroscopy, atomic force microscopy, and local nanoscale thermal analysis. The reaction mechanism among the CS, silane coupling agent, and natural rubber was studied, revealing that adhesion was optimized and cohesive failure achieved when 3-(trimethoxysilyl)propylamine (APS) was used to modify the CS. The CS was shown to be directly silanized by the silane coupling agents, but the reactions between the natural rubber and the silane coupling agents was dependent on silane functionality.